Fixed Pigmented Erythema Induced by Moringa oleifera: First Case Reported in Benin. - ADEGBIDI, HUGUES DANIEL GBADEBO; AKPADJAN, GBEMAWONMEDE FABRICE (My University, 2019)
Introduction: Fixed pigmented erythema (FPE) is one of the most common toxidermias worldwide. In Benin, it ranks first among toxidermias in hospitals. It is a skin reaction, usually due to drugs, but in recent years, foodborne cases of FPE have been described in the literature. To the best of our knowledge, no case of FPE due to Moringa has been described. We report the first case of FPE induced by Moringa oleifera in Benin. Observation: This was a 33-year-old atopic patient who had two episodes of pruritic skin lesions with pigmentary sequelae. During the second episode, the lesions were grafted onto the old seats. Each episode occurred 24 h after the leaves of M. oleifera were ingested. The diagnosis of FPE due to M. oleifera was beyond doubt. Therapeutic and preventive care has been provided. Conclusion: The interest of this observation lies not only in its originality but also and above all in the need to research the biochemical constituents of M. oleifera, to better know them.
Keywords: Fixed pigmented erythema; food origin; Moringa oleifera; toxidermy